Interpreting Studies and psycholinguistics: A possible synergy effect - Chmiel, Agnieszka (Benjamins, 2010)
Cognitive information processing has long been an area of interest for Interpreting Studies scholars. This paper discusses the interdisciplinary relation between Interpreting Studies (IS) and psycholinguistics as a source of a possible synergy effect and explains why Interpreting Studies matters not only to interpreters and interpreting researchers, but also to psycholinguists. First, the most significant contributions of psycholinguistics to interpreting research are identified, including in particular theoretical memory models and experimental methodology in mental lexicon studies. This is followed by an overview of the potential contribution of IS to psycholinguistics and bilingual studies. Conference interpreting is a unique case of bilingual/multilingual use of languages with more frequent code switching and greater inhibitory demands as compared to the non-interpreting use of language. Therefore, ‘bidirectional’ (A into B and B into A) and ‘unidirectional’ (C into A) interpreters and trainee interpreters are interesting experimental populations for mental lexicon studies and other cognitive studies. Finally, a progress report on COGSIMO, a research project aiming at leveraging the synergy of psycholinguistics and IS, will be presented. The project seeks to examine psycholinguistic processes and the skills of conference interpreting to establish efficient aptitude testing procedures for interpreter trainees based on cognitive predictors of success.
Keywords: psycholinguistics; interpreting studies; mental lexicon; cognitive studies; cognates; verbal fluency; bilingualism; directionality